The corona losses detection analysis at high voltage - Nugroho, Satrio Dwi; Setiabudy, Rudy (Universitas Negeri Padang, 2022)
The increasing use and use of electricity in Indonesia causes the potential for greater losses in the transmission and distribution system. This causes many problems that arise, one of which is the corona in the transmission and distribution system. Corona mapping can only be detected through several ways, namely sound, light and distinctive smell. In this thesis, the aim is to detect the corona with the characteristics of a distinctive sense of smell, then the results of the detection are compared with the calculated corona losses. This distinctive odor is the smell of ozone which is produced from ionization at high voltage with the surrounding air, namely oxygen to form ozone molecules that are not permanent. The metal electrode to be tested is the copper tip metal. After testing the voltage of the appearance of the corona occurs at 7kV, high voltage when testing the tip of the copper metal point at a voltage of 21 kV is greater than the corona losses. The greater the voltage, the greater the corona losses generated.